The Right to Family Life under the ECHR – with Special Regard to Central Europe - Garayová , Lilla (The ECHR at 70: The Central European Narrative, 2025)
This article delves into the interpretation the right to family life, as enshrined in Article 8 of the European Convention on Human Rights (ECHR), with a particular focus on the Central European context. It seeks to unravel how this right is interpreted and applied amidst the backdrop of evolving societal norms, legal developments, and cultural traditions unique to Central Europe. The analysis highlights the interplay between changing social attitudes, increased global mobility, economic challenges, and their collective impact on family-related matters. It explores the role of the family in child-rearing, societal advancement, and the personal development of its members, emphasising the deep-rooted connection between family life and cultural values. Furthermore, the paper examines the principle of the margin of appreciation and the doctrine of dynamic interpretation, as key legal mechanisms that navigate the balance between universal human rights protections and the respect for national sovereignty and cultural diversity. It reflects on the challenges and opportunities presented by the shifting perceptions of what constitutes a family in contemporary society, exploring the potential for legal frameworks to adapt to these changes while safeguarding fundamental rights. By providing an understanding of the right to family life from a Central European perspective, this paper contributes to the ongoing discourse on human rights, family law, and societal development.Keywords: Family life, protection of families, best interest of the child, children’s rights, ECHR, right to family life